The Development of Environmental Friendly Biological Sulfur Recovery Unit (BSRU) For Sulfur Coated Urea with Slow Release Fertilizer Method: A Case Study in Field X - Indriani, Erdila; Athallah, Fairuz; Despriadi, Eryko; Purnomosidi, Purnomosidi (Indonesian Journal on Geoscience, 2024)
The absorption of nitrogen from urea fertilizer is significantly inefficient. Due to its solubility in water. This problem can be overcome by producing slow-release fertilizer (SRF) that inhibits urea from being dissolved in water. Sulfur-coated urea (SCU) is one of the SRF methods. Therefore, this study aimed sulfur-coated slow-release urea fertilizer using sulfur waste from the Biological Sulfur Recovery Unit (BSRU) in Field X. A total of 14 tons of sulfur cake was produced daily by BSRU in Field X and sent to the laboratory for composition analysis, followed by drying. Subsequently, the dried sulfur was into a powder using a hammer and sieved to achieve a size of 200 mesh. Based on the results, SCU with the sulfur to urea ratio of 1:1 and mixing time of 15 minutes exhibited the best performance in dissolution tests with the longest dissolution time of 5 minutes which was better compared to the uncoated urea. After 7 days of observation, spinach that received SCU was more fertile and greener. The calculated NPV and payout time were 88712 million IDR and 1.76 years, respectively. This indicated that the development of this study was economically attractive. In conclusion, the value of sulfur waste from gas processing was increased by using sulfur waste from BSRU as a coating of urea while reducing related environmental effects.